Where do human sperm and egg meet?. Issue 1 (January 2021) - Thunnissen, Liselot J W; Cleypool, Cindy G J; de Bakker, Bernadette S
Abstract : Summary: Although it is commonly accepted that fertilisation in humans occurs in the ampulla of the fallopian tube, the peritoneal cavity might represent an alternative fertilisation site. Studies substantiating both fertilisation sites were reviewed and new insights on the fertilisation site in humans are discussed, including their implications for reproductive medicine.